Reseña de: Gabriela DE LIMA GRECCO, Burning Books, Awarding Writers. Literary Censorship in Francisco Franco’s Spain and Getulio Vargas’s Brazil, 1936-1945, Brighton-Chicago-Toronto, Sussex Academic Press, 2020 - Muñoz Soro, Javier (Historia del Presente, 2022)
-